Diffraction of (l,n)th mode Laguerre-Gaussian laser beam by a curved fork-shaped grating - Topuzoski, Suzana (Taylor&Francis Group, 2020)
The transformation of (l,n)th mode Laguerre-Gaussian (LG) laser beam, in the process of its diffraction by a curved fork-shaped grating with topological charge p, is theoretically studied. The analytical solutions for the diffracted wave field amplitudes are derived in the Fresnel regime and in the back focal plane of a convergent lens. The zeroth-diffraction order is found as (l,n)th mode LG beam. The higher, (±m)th diffraction-order beam is described in the radial direction through a product of the Gauss-doughnut function by the double sum of hypergeometric Kummer functions. Its topological charge can be increased or reduced compared to that of the incident beam, or it can be equal to zero. The radial intensity distributions are plotted and compared to the corresponding ones valid when a fork-shaped grating is used. The results are specialized for the cases of incident LG beams of modes (l, n = 0), (l = 0,n) and (l = 0,n = 0) i.e. Gaussian mode.
Keywords: Diffraction; Laguerre-Gaussian laser beam; curved fork-shaped grating; phase singularity; topological charge